Forced Convection in a Fluid Layer of Two Immiscible Fluids Occuping a Finite Height Over a Naturally Permeable Wall - Sacheti, N.C.; Bhargava, S.K.; Bhatt, B.S. (Engineering Transactions, 1988)
The paper examines the influence of a bounding naturally permeable wall on the velocity and temperature distributions in a fluid layer consisting of two immiscible. Newtonian fluids, the flow being caused by a constant pressure fradient. The solution has been obtained subject to a set of appropriate boundary and matching conditions linking various regions, including the B. J. condition at the porous interface. The effect of σ (porosity parameter) and y (the ratio of heights of upper and lower fluids) on various physical parameters of interest, has been shown graphically or through Tables.